Anomalous Temporoparietal Activity in Individuals with a Family History of Alcoholism: Studies from the Oklahoma Family Health Patterns Project. (21st May 2014) - Acheson, Ashley; Franklin, Crystal; Cohoon, Andrew J.; Glahn, David C.; Fox, Peter T.; Lovallo, William R.
<x xml:space="preserve">Abstract</x> Background Individuals with a family history of alcoholism (FH+) are at enhanced risk of developing alcohol or other substance use disorders relative to those with no family history (FH−). Alcoholics and FH+ subjects have greater interference scores on the Stroop color‐word task, suggesting these impairments may be a component of the cognitive phenotype of at‐risk individuals. Methods In this study, we examined whole‐brain activations in 24 FH+ and 28 FH− young adults performing the counting Stroop task, a variant of the Stroop task adapted for neuroimaging studies. Results Across all subjects, incongruent versus congruent comparisons showed activations in regions including parietal lobe areas, frontal eye fields, premotor areas, the anterior cingulate cortex, dorsolateral prefrontal cortex, and bilateral insula, indicating typical regions of activation involved in conflict resolution tasks. Compared with FH− participants, FH+ participants had greater activations in the left superior parietal lobule and precuneus (BA 7 and 19), inferior parietal lobule (BA 40), and middle temporal gyrus (BA 39 and 19), indicating a predominance of greater left hemisphere activity among FH+ in temporoparietal regions. There were no regions showing greater activations in the FH− group compared with the FH+ group. Conclusions These results are consistent with less efficient cognitive functioning potentially due to poorer communication over long pathways connecting temporoparietal regions to prefrontal brain regions that participate in a distributed network involved in cognitive processing and working memory necessary for conflict resolution.